Biopesticide based sustainable pest management for safer production of vegetable legumes and brassicas in Asia and Africa - Srinivasan, R.; Sevgan, S.; Ekesi, S.; Tamò, Manuele (Wiley, 2019)
Vegetables are one of the important crops which could alleviate the poverty and malnutrition among the smallholder farmers in tropical Asia and Africa. However, a plethora of pests limit the productivity of these crops, leading to economic losses. Vegetable producers overwhelmingly rely on chemical pesticides in order to reduce pest‐caused economic losses. However, over‐reliance on chemical pesticides poses serious threats to human and environmental health. Hence, biopesticides offer a viable alternative to chemical pesticides in sustainable pest management programs. Baculoviruses such as nucleopolyhedrovirus (NPV) and granulovirus (GV) have been exploited as successful biological pesticides in agriculture, horticulture and forestry. Maruca vitrata multiple nucleocapsid NPV (MaviMNPV) was found to be a unique baculovirus specifically infecting pod borer on food legumes, and it has been successfully developed as a biopesticide in Asia and Africa. Entomopathogenic fungi also offer sustainable pest management options. Several strains of Metarhizium anisopliae and Beauveria bassiana have been tested and developed as biopesticides in Asia and Africa. This review specifically focuses on the discovery and development of entomopathogenic virus and fungi‐based biopesticides against major pests of vegetable legumes and brassicas in Asia and Africa.